Education as a Petro-Pipeline: Beyond the Limits of Education Research in the Face of Climate Change - Karsgaard, Carrie; Shultz, Lynette (Canadian Journal of Education / Revue canadienne de l'éducation, 2025)
Considering the key cause of climate-harming carbon emissions is the increased use of fossil fuels, we might expect research in education to engage in petrocriticism—a critical way of reading the world that deconstructs how fossil-fuelled cultural expectations and practices, or “petroculture,” functions in education. To trace the intersection of fossil fuels and education, this article conducts a systematic literature review of both existing and emerging scholarship, engaging in a petrocritical reading of research themes to reveal the extent to which petroculture is naturalized and/or confronted. By examining both dominant research patterns and the notable silences, we conclude by making recommendations for how education scholarship can respond to climate science and contribute to a more livable future through research that takes up (a) petrocriticism, (b) mitigation and decarbonization, and (c) transformation toward alternatives.